2016
DOI: 10.1371/journal.pone.0152368
|View full text |Cite
|
Sign up to set email alerts
|

A Lower Proportion of Regulatory B Cells in Patients with Henoch–Schoenlein Purpura Nephritis

Abstract: BackgroundHenoch—Schoenlein purpura is the one of most common types of systemic vasculitis that involves impaired renal function and Henoch-Schoenlein purpura nephritis (HSPN). The diagnosis of this condition is largely based on immunohistologic detection of immunoglobulin A1-containing immune complex in the glomerular deposits of mesangium. Despite clinical advances, the etiopathogenesis of HSPN is still largely unknown.MethodsIn this study, we enrolled 25 newly diagnosed HSPN patients and 14 healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…The amounts of IL-10 + CD19 + and IL-10 + CD5 + CD1d + B cells, as well as the serum IL-10 concentration were significantly lower in Henoch–Schonlein purpura nephritis patients compared with healthy controls (HC); after treatment, they significantly increased. Meanwhile, the estimated glomerular filtration rate was also positively correlated with the amount of Bregs and the serum IL-10 concentration 54 . Although markers of Bregs might differ, a similar decrease or impairment of IL-10-producing B cells was also observed in patients with rheumatoid arthritis 44 , 55 57 , systemic lupus erythematosus (SLE) 24 , 55 , 58 , 59 , multiple sclerosis 26 , 55 , systemic sclerosis 60 , Myasthenia Gravis 61 , and other autoimmune diseases.…”
Section: Bregs Functions and Effectorsmentioning
confidence: 87%
“…The amounts of IL-10 + CD19 + and IL-10 + CD5 + CD1d + B cells, as well as the serum IL-10 concentration were significantly lower in Henoch–Schonlein purpura nephritis patients compared with healthy controls (HC); after treatment, they significantly increased. Meanwhile, the estimated glomerular filtration rate was also positively correlated with the amount of Bregs and the serum IL-10 concentration 54 . Although markers of Bregs might differ, a similar decrease or impairment of IL-10-producing B cells was also observed in patients with rheumatoid arthritis 44 , 55 57 , systemic lupus erythematosus (SLE) 24 , 55 , 58 , 59 , multiple sclerosis 26 , 55 , systemic sclerosis 60 , Myasthenia Gravis 61 , and other autoimmune diseases.…”
Section: Bregs Functions and Effectorsmentioning
confidence: 87%
“…[ 1 ] HSP is one of the most common small vasculitis in childhood, with clinical manifestations including nonthrombocytopenic purpura, arthritis or arthralgia, abdominal pain, gastrointestinal bleeding and so on. [ 2 , 3 ] Skin purpura and digestive tract symptoms are the most common complains in patients with this disease. [ 4 ] In the past decades, the incidence and recurrence of HSP were gradually increasing, which has invoked great interest of researchers globally.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] In the past decades, the incidence and recurrence of HSP were gradually increasing, which has invoked great interest of researchers globally. [ 2 5 ] In recent years, a large number of studies have shown that the intestinal tract of children with HSP has varying degrees of congestion, edema, erosion, ulcers, bleeding, and other morphological changes. [ 6 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…При ГВ выполнение нефробиопсии показано для оценки прогнозирования течения хронической болезни почек [12]. Как хорошо известно, наиболее типичным морфологическим признаком ГГН является наличие депозитов IgA в эндотелии капилляров и мезангиуме клубочков [11], а также гломерулярные отложения IgG, IgM, С3, C1q [18] и инфильтрация почечных структур клетками с рецепцией CD45 (фодрина) и CD68 (гликопротеина макросиалина) [14]. У взрослых больных примерно в 1/4-1/3 случаев ГГН встречается III морфологический тип (класс), тогда как у детей превалирует ІІ [17,24].…”
Section: ìàòåðèàë è ìåòîäûunclassified